Économie circulaire et écologie industrielle. Approche empirique à partir d’expériences de clusters et de territoires - Gwénaël Doré (Développement Durable et Territoires)
Today, business associations, clusters and local authorities are taking initiatives in the area of circular economy and, in particular, industrial and territorial ecology (EIT). These steps strengthen the local economy and the establishment of short circuits. Indeed, it appears that geographical proximity is most often necessary for the transfer of flows (energy, water, waste…). After recalling the definition of the main concepts, we analyze seven experiments in France. In particular, we note that these experiences are generally characterized by relatively weak financial and human resources, but that they require animation by a third-party actor.